Physical Health Problems of Internally Displaced Families in Rania City - Ameen, Barzan Mohammed; Mohammed , Rebwar Arsalan (Kufa Journal for Nursing Sciences, 2016)
Objective: To identify the physical health problems that face the displaced families in Rania District. Methodology: A descriptive (survey) study, quantitative design, was carried out in Rania District from 1st Nov-31st Dec, 2015. It included a purposive sample (non-probability) of (110) families who agreed to be part of this study. Data is collected through interviews by using formal questionnaire. The data are analyzed by application of descriptive statistical method. Results: The result of the study indicates that skin fungus (27.2%) and allergy (31.8%) are more common problems that happen after being displaced. In addition, after displacement hypertension and diabetes mellitus increased by 3.6%, and 2.7% respectively. Conclusion: The study concludes high prevalence rate of the chronic cases, allergy, and skin fungal infection are the main physical difficulties faced to the displaced people. Recommendation: Early screening, identification and management of chronic diseases among displaced people will be considered as priority step. In addition, providing health care vouchers to purchase the mediation is highly valuable for them.